Evaluating Risk Management Strategies in Fintech and Blockchain An Empirical Approach - Hartono, Tri; Putri Oganda, Fitra; Williams, Jack (APTISI Transactions on Management (ATM), 2025)
The rapid growth of fintech and blockchain technologies has revolution- ized the financial sector, introducing innovative solutions but also posing unique risks. Managing these risks effectively is crucial for ensuring the stability and sustainability of these technologies. This study aims to evaluate the effective- ness of risk management strategies in fintech and blockchain sectors, focusing on identifying the most adopted strategies and assessing their impact on mitigating various risks. A quantitative research design was employed, using surveys to collect data from industry experts in fintech and blockchain companies. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software to assess the relationships between risk management strategies and or- ganizational outcomes. The findings revealed that cybersecurity protocols, reg- ulatory compliance programs, and smart contract audits are the most commonly adopted risk management strategies. The study found that blockchain companies prioritize smart contract audits, while fintech companies focus more on cyber- security and regulatory compliance. Effective risk management strategies are crucial for the growth and stability of fintech and blockchain sectors. The study recommends that companies integrate advanced technologies and prioritize reg- ulatory compliance to mitigate risks and enhance trust.